The role of board of the directors in ensuring that the State-Owned Companies (SOCs) are sustainable in creating value to shareholders within the South African context - Mthombeni,Morris (University of Pretoria, 2018)
Mini Dissertation (MBA)--University of Pretoria, 2017.